Thread Tooth Modification of the Inverted Planetary Roller Screw Mechanism - Qiao Guan; Hao Zhipeng; Liao Rong; Zhang Nan; Liu Geng (Jixie chuandong)
Based on the thread tooth load distribution of the inverted planetary roller screw mechanism（IPRSM）, the influence of roller modification and screw modification on the load distribution is analyzed. The results show that the uneven load on the screw-roller interface is more serious than that on the long nut-roller interface, and the maximum contact stress and the maximum load on the threaded teeth are effectively reduced by the roller modification. Besides, the long nut-roller interface is more sensitive to the modification amount than that of the screw-roller interface. Similarly, the maximum load can also be effectively reduced by the screw modification. This study has some reference significance for optimizing the load distribution of the IPRSM.